2014
DOI: 10.25009/cpue.v0i19.966
|View full text |Cite
|
Sign up to set email alerts
|

La implementación de los Lineamientos para regular el expendio de alimentos y bebidas en dos escuelas telesecundarias de Veracruz. Análisis desde la perspectiva de los sujetos

Abstract: En este artículo se aborda la implementación de los Lineamientos Generales para el Expendio o Distribución de Alimentos y Bebidas en los Establecimientos de Consumo Escolar de los Planteles Educativos de Educación Básica de México. El análisis se basa en un estudio exploratorio de orientación cualitativa, apoyado en conceptos del análisis de políticas y del análisis político de discurso. El referente empírico se compone de testimonios de directivos, estudiantes, docentes y responsables de las tiendas de dos te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Also, studies in Mexico found that the schools lacked the space, food safety measures or the structure to implement these policies (38) . They also lacked a strong strategy to implement this throughout and faced difficulty in changing culturally strong practices, among others (39) . The evidence on the effectiveness of this strategy is considered weak as there are very limited studies.…”
Section: Population-wide or Community-based Programmes Or Initiativesmentioning
confidence: 99%
“…Also, studies in Mexico found that the schools lacked the space, food safety measures or the structure to implement these policies (38) . They also lacked a strong strategy to implement this throughout and faced difficulty in changing culturally strong practices, among others (39) . The evidence on the effectiveness of this strategy is considered weak as there are very limited studies.…”
Section: Population-wide or Community-based Programmes Or Initiativesmentioning
confidence: 99%
“…As the analysis of the NUTRE framework shows, regulations (mandatory and otherwise) often lack clear implementation, monitoring and evaluation strategies, key factors in the success of legal reforms [ 61 , 62 , 63 ]. Evidence also accounts for a lack of training and information of people meant to apply the new rules and, consequently, resistance to change [ 29 ]. Much more research is needed to guide government and public health advocates seeking to create effective SSB policies.…”
Section: Discussionmentioning
confidence: 99%
“…Available studies focus mainly on Mexico, where the National Agreement for Healthy Nutrition (ANSA, for its Spanish acronym) and its subsequent “General Guidelines to regulate the distribution of food and drinks at schools” [ 25 ] have reportedly encountered strong implementation barriers [ 4 , 26 , 27 , 28 ]. These limitations are mainly related to structural weaknesses [ 28 , 29 ], especially the lack of a strong official implementation strategy, that takes into account education regarding the policies, operational training, cultural barriers; and strategies to overcome the economic pressures of school beverage vendors [ 29 ]. The two studies assessing this issue in Mexico at the local level concluded that guidelines are generally not followed [ 29 , 30 ].…”
Section: Findings In Each Nutre Categorymentioning
confidence: 99%
See 2 more Smart Citations